Trends in broiler chicken meat production and food security in the sulaymaniyah governorate - Neima, Hemin Abubakir; Hassan, Khasraw Muheddin; Sirwan, Kawan; Hameed, Khansa (Emirates Journal of Food and Agriculture, 2023)
This study aims to report the trends in chicken meat production, importing, and per capita consumption in the Sulaymaniyah governorate, as well as, identify the challenges and opportunities of poultry sector development to become a substantial contributor to food security and poverty alleviation in the Kurdistan Region of Iraq (KRI). This study reviews ten years of data on the production of broiler chicken and per capita consumption patterns from 2011 to 2020, in the Sulaymaniyah governorate in KRI. The data from this study explain that more than half of the broiler chicken production projects are located in the Sulaymaniyah governorate. Thus, the growing number of poultry projects has significantly contributed to increasing local broiler chicken meat production by 6 folds and achieving 85.44% of self-sufficiency in broiler chicken meat production, even though their productivity is lower than their production capacity due to the high rate of broiler chicken mortality and uncertain supply chain management. Furthermore, frequent fluctuations and instability in the production rates are observed during the last decade, as broiler chicken meat production increased from 1,669.77 tonnes in 2011 to 20,034.06 tonne in 2015, then dropped to 11,802.36 tonnes in 2016 then rose again to 23,816.13 tonnes in 2019 and then declined again to 11,352.23 tonnes in 2020. These fluctuations and instabilities in local production may harm agri-food production sustainability and food security in the KRI in general, and, the Sulaymaniyah governorate in particular. Keywords: Poultry; Broiler chicken meat; Meat consumption; Food security; Sulaymaniyah; Kurdistan Region